2016
DOI: 10.2147/amep.s96481
|View full text |Cite
|
Sign up to set email alerts
|

Lecturing skills as predictors of tutoring skills in a problem-based medical curriculum

Abstract: PurposeRecruitment of tutors to work in problem-based learning (PBL) programs is challenging, especially in that most of them are graduated from discipline-based programs. Therefore, this study aims at examining whether lecturing skills of faculty could predict their PBL tutoring skills.MethodsThis study included evaluation of faculty (n=69) who participated in both tutoring and lecturing within particular PBL units at the College of Medicine and Medical Sciences (CMMS), Arabian Gulf University, Bahrain. Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Brazilian medical students believe that subjectmatter experts perform better for guiding the learning process than their non-expert counterparts [9]. Other authors agree with this concept [5,28,29,35].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Brazilian medical students believe that subjectmatter experts perform better for guiding the learning process than their non-expert counterparts [9]. Other authors agree with this concept [5,28,29,35].…”
Section: Discussionmentioning
confidence: 96%
“…In fact, there are evidences that tutors tend to over-rate students despite having evidence of poor performance ('halo effect') [11,30]. Despite the fact the process of rating students during tutorial sessions has been criticized [6,11,35], current evidences underscore that FA is a reliable indicator of students' summative learning achievement. Nevertheless, a crucial factor in this process is the qualification of the PBL facilitators [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…On account of limitations on instructor-conditions, teacher training is essential. Salah emphasized that effective PBL instructors required multiple skills that are positively related to their role in large group lectures, which could have implications for recruiting PBL instructors in medical programs [28]. Furthermore, peer teaching seems to be a good way to solve the shortage of teachers.…”
Section: Effect Of Instructors In Tbl and Pblmentioning
confidence: 99%
“…We have read with great interest the paper by Kassab et al 1 , who have essentially shown that good teachers will be good tutors in a problem-based learning (PBL) environment. We have been facing great difficulties to select tutors because there has been no tradition in PBL in our region in the preuniversity teaching.…”
Section: Dear Editormentioning
confidence: 99%